Persistent Systemic Microbial Translocation and Intestinal Damage During Coronavirus Disease-19 - Oliva, Alessandra; Miele, Maria Claudia; Di Timoteo, Federica; De Angelis, Massimiliano; Mauro, Vera; Aronica, Raissa; Al Ismail, Dania; Ceccarelli, Giancarlo; Pinacchio, Claudia; d’Ettorre, Gabriella; Mascellino, Maria Teresa; Mastroianni, Claudio M. (Frontiers in Immunology, 2021)
Microbial translocation (MT) and intestinal damage (ID) are poorly explored in COVID-19. Aims were to assess whether alteration of gut permeability and cell integrity characterize COVID-19 patients, whether it is more pronounced in severe infections and whether it influences the development of subsequent bloodstream infection (BSI). MT and ID markers during COVID-19 and Clostridioides difficile infection (CDI) were also compared. Over March–July 2020, 45 COVID-19 patients were enrolled. Markers of MT [LPB (Lipopolysacharide Binding Protein) and EndoCab IgM] and ID [I-FABP (Intestinal Fatty Acid Binding Protein)] were evaluated at COVID-19 diagnosis and after 7 days. Age- and gender-matched patients with CDI and, as a control group, healthy donors (HDs) were also included. Median age was 66 (56-71) years. Twenty-one (46.6%) were admitted to Intensive Care Unit (ICU) and mortality was 22% (10/45). Compared to HD, a high degree of MT and ID was observed. ICU patients had higher levels of MT, but not of ID, than non-ICU ones. Likewise, patients with BSI had lower EndoCab IgM than non-BSI. Lower MT and ID were observed in COVID-19 compared to CDI. Patients with COVID-19 exhibited high level of MT, especially subjects admitted to ICU. COVID-19 is associated with gut permeability.